Analisis Komposisi Bahan dan Uji Sensori Terhadap Beberapa Keju Olahan Komersil di Indonesia - Riandani, Andini Putri; Irfan, Yusuf; Supriyanto, Supriyanto; Intani, Arvita Emarilis; Kustiwan, Susan; Yanto, Ruli (JURNAL TEKNIK INDUSTRI, 2022)
The higher level of cheese consumption, an increase of 52% in the span of 5 years, opens up opportunities for the establishment of cheese factories. This study aimed to analyze the sensory differences of 3 processed cheese products on the market, namely MEG multipurpose cheese (KM), Kraft Cheddar (KK), and Prochiz Gold (KP). Sensory analysis was carried out on 3 samples using a descriptive test on 13 semi-trained panelists. The results of this study were that the panelists preferred KK because it had a distinctive milky aroma and a strong cheese characteristic; stronger milk, cheese, savory, salty flavors; good sliceability; softer texture and mouthfeel. However, for grated results, panelists prefer KP because it had a intact and neat grater product.